2009
DOI: 10.1007/s10551-009-0113-1
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Communications and Corporate Social Responsibility (CSR): Marriage of Convenience or Shotgun Wedding?

Abstract: marketing, marketing communications, corporate social responsibility, ethics,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
198
0
14

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(217 citation statements)
references
References 32 publications
5
198
0
14
Order By: Relevance
“…These are often the result of irrelevant ethical claims or 'greenwashing' which mislead by stressing the supposed environmental credentials, where these are unsubstantiated (Gillespie, 2008;Jahdi & Acikdilli, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…These are often the result of irrelevant ethical claims or 'greenwashing' which mislead by stressing the supposed environmental credentials, where these are unsubstantiated (Gillespie, 2008;Jahdi & Acikdilli, 2009). …”
Section: Literature Reviewmentioning
confidence: 99%
“…state-of-the-art [8][9][10]14,15] reveals a clear interest from many authors in performing such a study, although no such research has ever attempted to address this issue so completely. The set of reports analyzed in this study belong to a single sector, as previous research has shown that reporting practices vary as a function of the activity sector [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some others argue companies should only focus on their business leaving all other aims to specific organizations like public offices, NGOs, business associations, etc. (see [4,7,9] for some reflections). Or, to finish with other examples, some authors believe CSR should not be more than "good will", other authors believe CSR is little more than bureaucracy, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations